Language-Based Software Testing. - Steinhöfel, Dominic; Zeller, Andreas (Communications of the ACM, 2024)
The article explores the potential for language-based testing bots to conduct software testing. First, the authors detail the requirements of a software testing bot including input generation as well as output evaluation. Then, an investigation of the incorporation of grammars with constraints in order to satisfy both syntax and semantics of inputs and outputs are presented utilizing the authors' open source tool ILSa (Input Specification Language).